(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2020)
Don Quixote arrives in Barcelona at sunrise on Saint John’s day, a traditional Christian festivity that had adapted some ancient popular festivals which celebrated the summer solstice. That context was a clear foreboding that Cervantes’ characters were to live the turning points of their adventures: Cervantes intended them to arrive to Barcelona on such a symbolic date. In mid-twentieth century, four great Spanish novelists, namely Carmen Laforet, Luis Romero, Juan Marsé and Eduardo Mendoza, retrieved the motif which had been created by Cervantes and used it in some of their major works. This article tracks and analyses the appearance of such a setting as Barcelona at sunrise on Saint’s John day in the books Nada, La Noria, Últimas tardes con Teresa and La verdad sobre el caso Savolta. Keywords: Don Quixote, Carmen Laforet, Luis Romero, Juan Marsé, Eduardo Mendoza.